ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PEMBELIAN BUAH SALAK DI AGROWISATA OMAH SALAK KECAMATAN TURI KABUPATEN SLEMAN - Ahmad Abdul Latif (Universitas Pasir Pengaraian, 2020)
This research aims to the effect of total purchase salak fruits and to determine of variable salak prices, the price of orange, household income of consumers, family size of consumers, taste of consumers, and the attractiveness of agritourism that affect the total purchase of salak fruits in Omah Salak Agritourism. This research was carried out in June to August 2019. The research location determined by purposive at Omah Salak Agritourism in sub-district Turi, Sleman regency. This research was used survey method with 100 people who consume the salak fruits taken by accidental sampling. The data analytical method used multiple linear regression. The result showed the average of salak purchases at Agro Tourism Omah Salak 5,3 kg ​​and the most fruit is salak pondoh super. The variable of salak price (X1), the price of orange (X2), household income of consumers (X3), family size of consumers (X4), taste of consumers (X5) and the attractiveness of agritourism simultaneously have real effect on the total purchase of salak fruits in Omah Salak Agritourism. Partially the variable of household income of consumers (X3), family size of consumers (X4), and the taste of consumers (X5) have real effect on the total purchase of salak fruits. The variable of price of salak price (X1), price of orange(X2) have no real effect on the total purchase of salak fruits in Omah Salak Agritourism.